Foreign Ownership, Agency Fees, Debt, and Company Value of Manufacturing Companies on the Indonesia Stock Exchange - Budiman, Alvin; Mahadwartha, Putu Anom (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
This research aims to test the effect of foreign ownership, agency cost, and debt on firm value. The Independent variable used in this research is foreign ownership, measured by the percentage of foreign ownership; agency cost, measured by asset utilization; and debt, measured by debt ratio. The dependent variable of this research is a firm value measured by Tobin